К вопросу повышения эффективности процесса обучения базовой технике двигательных действий борцов вольного стиля на этапе начальной подготовки - Тупеев, Юлай; Tupeev, Ylay (Східноєвропейський національній університет ім. Лесі Українки, 2013)
В работе установлено, что основой для построения и коррекции учебно-тренировочного процесса юных борцов вольного стиля являться объективные данные последовательности обучения базовым приёмам техники борьбы в стойке и партере. Представлены структура и возможности разработанной информационно- методической системы «Чемпион». Методические подходы начального обучения технике двигательных действий с использованием мультимедийной информационно-методической системы «Чемпион» основываются на принципах направленности обучения на создание базовой школы техники двигательных действий. In this work is found that the basis for the construction and correction of the young freestyle wrestler’s training process are objective data about the studying sequence of basic wrestling techniques in the standing and parterre. The structure and the capabilities of the developed information and methodology system «Champion» are presented. Methodological approaches for early training to technique of motor actions with using of multimedia information and methodology system «Champion» are based on the principles of training orientation to the formation of basic school of motor actions technique.
The Problem of Increasing of Training Process Efficiency of Basic Techniques of Freestyle Wrestler’s Motor Actions at Early Preparartion Stage
Keywords: информационно-методическая система; спортивная борьба; обучение; техника; information and methodological system; wrestling; training; technique